Silencing the livin gene enhances the cytotoxic effects of anticancer drugs on colon cancer cells - Oh, Bo Young (Ann Surg Treat Res, 2016)
PURPOSE: Livin is associated with drug response in several cancers. The aim of this study was to investigate the effect of silencing the livin gene expression on anticancer drug response in colorectal cancer. METHODS: siRNA was transfected at different concentrations (0, 10, and 30nM) into HCT116 cells, then cells were treated with either 5-fluorouracil (FU)/leucovorin (LV) or oxaliplatin (L-OHP)/5-FU/LV. Cellular viability and apoptosis were evaluated following silencing of livin gene expression combined with treatment with anticancer drugs. RESULTS: Livin gene expression was effectively suppressed by 30nM siRNA compared with control and 10nM siRNA. The 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay showed that proliferation was effectively inhibited in cells treated with a combination of both siRNA and an anticancer drug, compared to cells treated with siRNA-Livin or anticancer drug alone. In particular, the combination of 30nM siRNA and L-OHP/5-FU/LV resulted in a 93.8% and 91.4% decrease, compared to untreated control or L-OHP/5-FU/LV alone, respectively. Cellular proliferation was most effectively suppressed by a combination of 30nM of siRNA and L-OHP/5-FU/LV compared to other combinations. CONCLUSION: siRNA-mediated down-regulation of livin gene expression could significantly suppress colon cancer growth and enhance the cytotoxic effects of anticancer drugs such as 5-FU and L-OHP. The results of this study suggest that silencing livin gene expression in combination with treatment with anticancer drugs might be a novel cancer therapy for colorectal cancer.